A Case Report of Dicephalus Dipus Dibrachius –A Rare Variant of Conjoined Twins - Rama, Kaanthi; Jahagirdar, Vinay; Gouri, Tati Indira; Vadagandla, Koteshwareddy; Rama, Amulya (Archives of Clinical and Medical Case Reports, 2020)
Conjoint twins are a rare type of monoamniotic twins, with an estimated incidence of 1.5 per 100,000 births worldwide. Fusion occurs between same body parts due to a defect in embryological development. Cardiovascular and other congenital anomalies lead to dismal prognosis with conjoined twins. Early prenatal diagnosis can help in parental counseling regarding the management of pregnancy, including termination or post-natal surgical separation. Ultrasonography and other imaging techniques are vital in making the anatomical survey for evaluating future options. We report a rare variant of conjoined twins, Dicephalus Dipus Dibrachius, where the fetus has two heads, but a single trunk, with two upper and two lower limbs, diagnosed at 9 weeks and 4 days of gestation, with the help of ultrasonography and color Doppler imaging. <gdiv></gdiv>